Study of prevalence and risk factors for depression and anxiety among chronic pain patients in Hospital Universiti Sains Malaysia - Sukri, Rosaidaremanja (2020)
Background Psychological disorder namely anxiety and depression often co-exist in chronic pain patient. Likewise affective disorder more likely to express pain differently. Concomitant anxiety and depression in chronic pain were difficult and challenging to manage. To date, the predisposing factors to these affective disorder were largely inconclusive. Aim To determine prevalence of anxiety and depression among Chronic pain patient as well as to determine association between anxiety and depression among chronic pain patient. and to predict factor associated with anxiety and chronic pain. Methods 116 of patients with chronic pain were given set of questions related to their general well-being and demographic details. Question contains HADS-A and HADS-D either in original English and validated Malay version. The severity of anxiety and depression were recorded and analysed. Results Prevalence of anxiety and depression were 28.4% and 26.7% respectively. Anxiety had a positive association with depression among chronic pain patient. Factors such as age, gender, race, educational status, employment status, income, severity of pain, age of diagnosis, duration of pain, treatment of pain did not predict depression . However employment, income, duration of pain, diagnosis age, and etiology of pain can predict anxiety. Conclusion The relationship between depression and anxiety with chronic pain were complex. Affective disorder can occurs as result of chronic pain and vice versa. Anxiety and depression has significant positive association. Addition of the screening of anxiety and depression in chronic pain patient who come for treatment may help in timely manage their affective disorder as well as helping in their chronic pain.